If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(47 + -80) = 0 Combine like terms: 47 + -80 = -33 -1(-33) = 0 Multiply -1 * -33 33 = 0 Solving 33 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 9x*2-6x+1=0 | | (X+6)(x+12)= | | 2x+9+4x+4=43 | | -2(x-5)=-112 | | 14a+17=101 | | 6(x+3)-(2x-8)= | | 5x+3+7x+2=89 | | 8=6(4+x) | | -9(1-16x)=30x-9 | | 3n^3-100=n | | (4Y+1)-(-3Y-7)=3 | | 3+2(x-3)=17 | | -(3x-8y+2)= | | 0.25X+0.05(16-X)=0.10(24) | | 8(b+5)=2(b+4) | | 7c+13-5=29 | | N-14-3n-10=2-3n+10-3n | | 0=2*x*cox(x)-x | | 2x^2-22=28 | | 7x+x^2-24=0 | | 2n+9=-25 | | 15+9b=114 | | 2t+3=99 | | (19b-2)-6(3b+3)=-4 | | 9+x(-4)=13 | | 2(6-3x-5x)+6(2x+8)=28 | | n^2-68=18n | | -3(3p+4)-2(1-11p)=3(6+4p) | | 0=-3x+15 | | 2(6x-3x-5x)+6(2x+8)=28 | | (4+2)2+(6-3)2= | | -4(3x-5x+6)= |